INTEGRASI OVOP DAN DIGITALISASI DALAM PENGEMBANGAN UMKM DESA: STUDI KASUS DESA KARANGGAN - Kusuma Wardani; Bunga Febriana; Darliana Cantika Sari; Fauzan Akmaludin; Raeyna Putri Hermawan; Berlina Wulandari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the implementation of UMKM digitalization through the One Village One Product (OVOP) approach in supporting local economic development in Karanggan Village. The study employs a qualitative approach with data collected through interviews and observations. The results indicate that digitalization through QRIS usage, Google Maps utilization, and digital marketing training improves business visibility and UMKM actors’ understanding of technology. However, challenges remain in terms of limited digital literacy and internet access. This study concludes that the integration of OVOP and digitalization is an effective strategy to enhance UMKM competitiveness.